Influence of TICs learning in the Biomedical Science - Moreno Garcia, Maria Florencia (2016)
Introduction: TICs represent a key to carry out actions that lead to the formation element and learning, such as content submission, implementation of activities and learning assessment. Objectives: - To assess the student in the subject Hemostasis by using multimedia (interactive videos). - To determine the influence of TICs in the rapid acquisition of knowledge. Materials and Methods: We worked with a sample of 50 students, which was divided into two groups: Group 1 (control), Group 2 (multimedia material). Students attended classes of the subject Hemostasis. Group 1 had only oral exposure of the subject while Group 2 also received support from the lecture with multimedia material. Immediately in both groups a written evaluation of the subject was made consisting of ten multiple choice questions related to the topic and to the interactive video. SPSS version 23 for the statistical treatment of the data was used. Results: written assessment of only four responses were statistically significant, difference favoring learning in the group that received a lecture with the support of interactive videos over the group that only received a conventional lecture (p <0.05). It could be determined that learning was facilitated by the use of TICs in group 2. Conclusions: Promoting the use of TICs together with lectures could a useful resource for the rapid incorporation of knowledge